Ludwik Sternbach felicitation volume = Luḍvika Sṭarnabāḵẖa abhinandana grantha - Sternbach, Ludwik; Sinha, J. P. (Jagdamba Prasad), 1933- (Akhila Bharatiya Sanskrit Parishad, 1979)
Felicitation volume honoring Ludwik Sternbach, Indologist, b. 1909, on the occasion of his 70th birthday; includes contributors' bio-data.